Alkali-thermal activation on red mud and its potential for preparing one-part geopolymer - Nan Ye; Xinyuan Ke; Cheng Xiang; Huabin Wang; Yang. Jiakuan (International Mineral Processing Congress, 2014)
Bayer red mud is a highly alkaline residue produced by the alumina industry through the Bayer process. Its disposal is a worldwide problem. The high alkali content and poor pozzolanic activity is aconstraint for its utilization on construction materials. In this study, the red mud was activated through an alkali-thermal method to improve its activity so that it can be utilized in geopolymerization. The red mud was mixed with different amounts of sodium hydroxide, and calcined under 800 °C to produce geopolymer precursors, and then mixed with water directly to prepare one-part geopolymer. X-ray diffraction was conducted to study the phase transformation of red mud and the mechanism of its geopolymerization. Nitrogen Isothermal Adsorption tests were conducted to analyze the pore structure of the geopolymer binders. The results show that calcinations with alkali would promote the Al in red mud transforming into glassy SiO2 to form the N-A-S phase which is soluble in water. When the red mud was calcined at 800 °C with a Na2O addition more than 10%, the dissolving of Si and Al from red mud was greatly improved. The thermal-alkali activated red mud with 10% Na2O obtaining a compressive strength of 9.77 MPa after it reacted with water and cured for 7 days at 20 °C and 95% RH. But the strength decreased as the curing time extended to 28 days. The reason is suggested to be that the polymerization of Al-O and Si-O is unstable due to the low Si/Al ratio of red mud. The alkali in the structure dissolves again into the pore water and corrupts the pore structure. Therefore, the thermal-alkali red mud should be combined with other reactive aluminosilicate materials such as granulated blast furnace slag to absorb the alkali released by the thermal-alkali red mud at the latter curing days.